Seeding Rate for Dryland Wheat - A. Schlegel; J. D. Holman; L. Haag (Kansas Agricultural Experiment Station Research Reports, 2016)
Four winter wheat varieties (Plainsgold Byrd, Limagrain T158, Syngenta TAM 111, and WestBred Winterhawk) were planted at five seeding rates (30, 45, 60, 75, and 90 lb/a) in the fall of 2014 at Colby, Garden City, and Tribune, KS. The objective of the study is to identify appropriate seeding rates for dryland winter wheat in western Kansas. Averaged across varieties, a seeding rate of 60 lb/a seemed to be adequate at all locations in 2015. The wheat variety T158 was the highest yielding (or in the highest group) at all locations. Other varieties may have been affected by differential response to stripe rust and winter injury resulting in lower yields. Variety selection appears to have more effect on wheat yields than seeding rate.
Keywords: dryland wheat; seeding rate